2014
DOI: 10.1111/all.12520
|View full text |Cite
|
Sign up to set email alerts
|

A novel assay to diagnose hereditary angioedema utilizing inhibition of bradykinin-forming enzymes

Abstract: Background: Hereditary angioedema types I and II are caused by a functional deficiency of C1 inhibitor (C1-INH), leading to overproduction of bradykinin. The current functional diagnostic assays employ inhibition of activated C1s; however, an alternative, more physiologic method is desirable. Methods: ELISAs were developed using biotinylated activated factor XII (factor XIIa) or biotinylated kallikrein bound to avidin-coated plates. Incubation with plasma was followed by detection of bound C1-INH. Results: Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…Methods using contact‐phase proteins had already been introduced in the literature. Recently, an assay took advantage of an ELISA method using biotinylated active enzymes (FXIIa or KK) . Its rationale was founded on the formation of FXIIa–C1Inh and KK–C1Inh complexes after incubation with plasma and detection of bound C1Inh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods using contact‐phase proteins had already been introduced in the literature. Recently, an assay took advantage of an ELISA method using biotinylated active enzymes (FXIIa or KK) . Its rationale was founded on the formation of FXIIa–C1Inh and KK–C1Inh complexes after incubation with plasma and detection of bound C1Inh.…”
Section: Discussionmentioning
confidence: 99%
“…However, the primary mediator of swelling in angioedema patients is BK, whose production is controlled by plasma KK. A recent approach used biotinylated active enzymes (FXIIa or KK) and took advantage of the abundance of enzyme–C1Inh complex as a readout of the C1Inh function in plasma . The authors demonstrated high sensitivity using FXIIa, while C1Inh targeted only 60% of the protease when using KK, presumably due to its inhibition by α2M.…”
mentioning
confidence: 99%
“…A novel assay for the diagnosis of HAE types I and II based on the inhibition of BK-forming enzymes has been recently proposed. It seems to perform better than both the commonly used ELISA and the chromogenic assay as well [66].…”
Section: Unmet Needs and Future Directionsmentioning
confidence: 92%
“…Diagnosis of nC1Inh-AE is still controversial: detection of F12 gene mutation is pertinent only to FXII-AE but cannot explain why many carriers are asymptomatic [ 13 , 14 ]. Enzymatic tests have been performed to investigate increased kinin-forming conditions [ 26 ], C1Inh-protease complexes [ 27 ] or defective kinin catabolism [ 13 , 28 ]. While some of these tests are already used in AE classification [ 2 ], their consensual use is still pending on pre-analytical and enzymatic considerations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%